2022
DOI: 10.1002/hon.2974
|View full text |Cite
|
Sign up to set email alerts
|

Successful early use of anti‐SARS‐CoV‐2 monoclonal neutralizing antibodies in SARS‐CoV‐2 infected hematological patients – A Czech multicenter experience

Abstract: COVID-19 significantly impairs survival rates among hematological patients when compared to the general population. Our prospective multicentre project analyzed early administration of anti-SARS-CoV-2 spike protein neutralizing monoclonal antibodies (NmAbs) -bamlanivimab (72%) and casirivimab/imdevimab (28%) -efficacy among hematological patients with early-stage COVID-19. Mortality rate was compared to a control cohort of 575 SARS-CoV-2 positive hematological patients untreated with any specific anti-COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
8
25
0
1
Order By: Relevance
“…Age, sex, high BMI, diabetes, renal and liver impairment, hemoglobinopathies, neurodegenerative diseases, cardiovascular and pulmonary co-morbidities, as well as immunocompromission, have been associated with hospitalization and severe course of COVID-19 both in adolescents and adult patients, thus leading to prioritization for specific early treatment ( 41 43 ). In real-world studies, early treatment (within 5 days of symptom onset) with monoclonal antibodies or antivirals was associated with significant reduction in hospital admission, severe disease and hospitalization ( 11 13 , 15 , 28 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, sex, high BMI, diabetes, renal and liver impairment, hemoglobinopathies, neurodegenerative diseases, cardiovascular and pulmonary co-morbidities, as well as immunocompromission, have been associated with hospitalization and severe course of COVID-19 both in adolescents and adult patients, thus leading to prioritization for specific early treatment ( 41 43 ). In real-world studies, early treatment (within 5 days of symptom onset) with monoclonal antibodies or antivirals was associated with significant reduction in hospital admission, severe disease and hospitalization ( 11 13 , 15 , 28 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable patients such as those with hematological, oncological and respiratory diseases, and immunocompromised patients including those with Inborn Errors of Immunity (IEI) had the chance to be treated with mabs because of significant risk for severe COVID-19. Different experiences associated with positive outcomes in terms of hospitalization and mortality have been reported in COVID-19 fragile categories, such as kidney transplant recipients and hematological patients ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the BLAZE-1 study included a very low number of participants with either pre-existing immunologic conditions or concomitant treatment with immunosuppressive agents (1.5% and 4.9%, respectively). Further information on the use of early treatment for COVID-19 among immunocompromised patients is provided by other single-centre observational studies and case series, mostly regarding the administration of bamlanivimab, bamlanivimab/etesevimab, and casirivimab/imdevimab [ 18 , 19 , 20 , 21 , 22 ]. Despite the small number of patients enrolled and the inherent biases, these studies contributed to corroborating the safety profile and the therapeutic role of mAbs in nonhospitalized immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…A further point to consider is that the patient experienced a resolution of symptoms and viral clearance of nasopharyngeal swab after the administration of sotrovimab. A prospective multicenter study demonstrated that bamlanivimab and casirivimab/imdevimab were effective in reducing disease progression and mortality among hematological patients in early stages of SARS-CoV-2 infection [ 17 ]. However, data on the efficacy of sotrovimab in cancer patients infected with the Omicron variant, especially after sustained exposure to therapeutic anti-CD20 antibodies, are still lacking.…”
Section: Discussionmentioning
confidence: 99%